MOSQUE AFFILIATED SCHOOLS AND TARIQA ABODES OF DZHAR MUNICIPALITY (ACCORDING TO FIELD MATERIAL) - Halaev, Zahid Alievic (History, Archeology and Ethnography of the Caucasus, 2020)
Mosque affiliated schools – madrasah and hujra (الهجرة) – had a significant impact on the spread of Islamic religious thought. There were a number of tariqa abodes in many villages of both Zakatala district and different regions of the North Caucasus in the pre-revolutionary period. These abodes were not educational institutions in the modern sense. They would often be built at the expense of the villagers, sponsors, or an individual clan (tukhum); the abode then received the name of its benefactor. Hujra could be placed in a mullah’s house or in a house of any other religious figure, who kindly offered the quarters for religious needs, including tariqa rituals.In the present paper, on the basis of field work, we make an attempt to consider the creation of hujras both as tariqa abodes and as schools at mosques, on the example of the modern Dzhar municipality of the Zakatala district of the Republic of Azerbaijan. The author of the article does not intend to see into the issues related to the Muslim education system, programs, methods and teaching methods, since they are the subject of a separate study. The paper proposes the information on the construction of hujras, analyzes a number of inscriptions, discovered during the field work, gives a polygraphic description of the inscriptions, accompanied by commentaries, translations and transliterations. In some abodes, no traces of inscriptions were found. The analysis of the material shows that at the turn of the 19–20th centuries in the Zakatala area, many educational Muslim institutions were built. The inscriptions revealed and published allow us to determine the date of the construction of religious buildings, give us information on the names of religious figures and the benefactors, who participated in the construction works.
Keywords: Russian Empire; Zakatala district; 19th century; Dzhar; Islam; tariqa; religious figures; hujra; abode; tukhum; community.